The correlation between rheumatoid factor and anti cyclic citrullinated peptides with gene expression of FoxP3 in rheumatoid artheritis patients - Nasrin Iranshahi; Seyed Mojtaba Amiri; Parisa Zafari; Mahdi Taghaddosi (International Journal of Biomedicine and Public Health, 2018)
Introduction: Rheumatoid arthritis (RA) is a chronic autoimmune disorder that affect 1-2% of people worldwide. Inflammation is an important factor in the pathogenesis of RA. Anti- Cyclic Citrullinated Peptid (Anti-CCP) antibody and Rheumatoid Factor (RF) are autoantibodies that promotes inflammatory reactions and have a crucial role in RA pathogenesis. Treg cells are necessary for the maintenance of immune homeostasis and prevention of autoimmunity. FoxP3 is essential transcription factor for development of these regulatory cells. In this study, we surveyed the effects of FoxP3 gene expression in peripheral blood on plasma levels of Anti-CCP and RF. Methods: Peripheral blood samples were collected from 47 patients and 44 healthy subjects. Then plasma levels of Anti-CCP have been evaluated using ELISA method. Also RF was detected with latex agglutination test, and gene expression of FoxP3 analyzed by real time PCR . Results: The amount of Anti-CCP and RF were significantly higher in our patients in comparison with healthy subjects (P<0.001) and (P< 0.001) respectively. Also significant reverse correlation between RF and Anti-CCP with gene expression of FoxP3 have been shown in our study (r: -0.630, r: -0.584) respectivly. The sensitivity and specificity of Anti-CCP and RF was (89.1%, 86.95%) and (91.3%, 91.1%) respectively for the diagnosis of RA. Conclusion: Our data illustrated that FoxP3 gene expression have reverse significant correlation with plasma concentration of anti-CCP and RF.